(untitled) (International Journal of Engineering and Computer Science, 2016)
Non homogeneous Poisson process software reliability models assume perfect debugging. However in the testing process there is a chance of introducing new faults when detected faults are removed. A model with this concept is called imperfect debugging software reliability model. Imperfect debugging software reliability models proposed in the literature assume a constant or monotonically decreasing fault introduction function. In this article we propose a software reliability model that considers Rayleigh distribution fault content function. The model can capture increasing/decreasing nature of fault introduction rate per fault. The parameters of the model are estimated using maximum likelihood method. A real data are used to verify the model.